Lindian Chronicle Connections: Contrasting Rhodian Networks Real and Imagined - Callaghan, Gregory J. (Journal of Historical Network Research, 2022)
The votives described in the Lindian Chronicle, a late Hellenistic inscription from the Sanctuary of Athena Lindia on Rhodes, create a clear but largely fictitious network stretching across the Eastern Mediterranean. This paper diagrams the network captured by this text, and then seeks to explain why it was invoked by the Lindians at this particular historical moment (100 BCE). This secondary goal is accomplished by considering archaeological and textual evidence for Rhodian trade in the second half of the 2nd c. BCE, and comparing the resulting ‘real’ trade network with the ‘imagined’ network of the inscription. This comparison leads to the conclusion that the network of the Lindian Chronicle was invoked to reassure the local populace of Rhodes’ historical and unshakable importance in Mediterranean interstate trade, at a time when that trade—the life blood of the island—had precipitously dropped.